SINERGITAS PUBLIC RELATIONS PT. PLN (PERSERO) WILAYAH SULAWESI SELATAN TENGGARA DENGAN MEDIA MASSA DALAM UPAYA PEMENUHAN KEPUASAN PELANGGAN - Muhammad Akbar (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
The aim of the study was to find out the planning and implementation of the public relations activities and the relationships between the customer's satisfaction and the public relations activities of PT. PLN (Persero) Regional South and Southeast Sulawesi.In order to achieve my aim, the writer used institutional research. The analysis was done descriptively and qualitatively.The results of the study indicate mat the public relations planning activities carried out by PT. PLN (Persero) Regional South and Southeast Sulawesi have not been applied thoroughly; however, the implementation of the activities have applied the functions and the principles of public relations.